2014
DOI: 10.1371/journal.pone.0090018
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Exhaled Nitric Oxide in Allergen-Provoked Asthma Is Associated with Airway Epithelial iNOS

Abstract: BackgroundFractional exhaled nitric oxide is elevated in allergen-provoked asthma. The cellular and molecular source of the elevated fractional exhaled nitric oxide is, however, uncertain.ObjectiveTo investigate whether fractional exhaled nitric oxide is associated with increased airway epithelial inducible nitric oxide synthase (iNOS) in allergen-provoked asthma.MethodsFractional exhaled nitric oxide was measured in healthy controls (n = 14) and allergic asthmatics (n = 12), before and after bronchial provoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 29 publications
0
46
0
2
Order By: Relevance
“…Specifically, the airway epithelium may be a major source of IL-25, which regulates immune-mediated inflammatory airway diseases and the response to infections, and IL-33 and thymic stromal lymphopoietin, which also influence asthma development (47). Moreover, recent studies have found that epithelial barrier, epithelial mesenchymal transition, and mesenchymal phenotype are associated with lung function and allergic pulmonary diseases over the life course (47)(48)(49)(50). Factors involved in airway epithelial function and migration have been increasingly implicated in the links between PM, impaired lung growth, and asthma risk (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the airway epithelium may be a major source of IL-25, which regulates immune-mediated inflammatory airway diseases and the response to infections, and IL-33 and thymic stromal lymphopoietin, which also influence asthma development (47). Moreover, recent studies have found that epithelial barrier, epithelial mesenchymal transition, and mesenchymal phenotype are associated with lung function and allergic pulmonary diseases over the life course (47)(48)(49)(50). Factors involved in airway epithelial function and migration have been increasingly implicated in the links between PM, impaired lung growth, and asthma risk (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…4 In the vascular system, the excessive amount of NO produced by iNOS is associated with decreased function of eNOS and subsequent impairment of both vasoconstriction and endothelium-dependent vasorelaxation. 6,7 Furthermore, the iNOSdependent detrimental overproduction of NO and related species such as peroxynitrites are implicated also in pathophysiological conditions such as asthma, 8 hypertension, 9 inflammatory bowel disease, 10 and cancer. 11,12 Selective inhibition of iNOS could therefore represent a feasible therapeutic strategy to treat the aforementioned and other conditions, and intense efforts to identify selective iNOS inhibitors have been carried out.…”
mentioning
confidence: 99%
“…Given that environmental factors are known to induce NOS activity and modify FeNO [6,7,11,12], we hypothesised that FeNO measured after birth, and before relevant exposure to these factors, is not associated with asthma at school age.…”
mentioning
confidence: 99%
“…In model 2, environmental factors (e.g. infections or air pollution) are needed to induce iNOS [6,7,11], which then results in elevated FeNO. In this hypothesis, we would expect no association between FeNO at birth (measured before environmental exposures) and school-age outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation